Indirect speech acts and persuasive strategies of cultural narratives of Go’et in health promotion - Daar, Gabriel Fredi; Fithriyah Inda Nur Abida; Lisetyo Ariyanti; Rahayu Kuswardani (Politeknik Negeri Bali, 2025)
Studies of cultural narratives as indirect speech acts and persuasive strategies in health promotion remain limited. This study aims to discover how